Strategy of Women Micro Enterprises in Managing Micro Financing at Mawaridussalam Micro Waqf Bank - Mahfuzah, Mahfuzah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Women are a gender that has difficulty gaining economic access, especially access to capital. Even though women have high potential to increase family income, and even drive the national economy. Moreover, there are many small business sectors in Indonesia. This sector is usually delegated to women because women are tied to domestic work (Rozalinda, 2014). Domestic work is assigned to women, making women more involved in informal businesses. This business is a small and simple household-based business. Even though they have opportunities and opportunities to develop in informal businesses, this group of women small business actors still often have problems in getting access to capital. The result is that the business they own does not experience rapid development. Apart from that, women's conditions are worsened by the lack of knowledge, skills, and networks to develop and expand their businesses. Therefore, the government through the Financial Services Authority (OJK) initiated the establishment of a Micro Waqf Bank (BWM). The target of BWM is small, productive communities around Islamic boarding schools (Balqis, WG, & Sartono, 2019). Based on the statement that the cumulative increase in the amount of financing provided by BWM Mawaridussalam to women’s micro businesses has not been in line with the increase in customer business development. The formulation of the problem in this research is the conditions and strategies of women’s businesses that obtain and manage financing from BWM Mawaridussalam. The aim is to find out the conditions and strategies of women’s businesses that obtain and manage financing from BWM Mawaridussalam. Researcher used the SWOT analysis method. The results of the research are that the strategy that has been carried out so far is in defensive status. The meaning is to minimize weaknesses and avoid threats. Currently, female micro business actors have many weaknesses and are facing big challenges. Among them, namely: first, discipline in financial recording. Second, Separate personal finances from business finances. Third, a strong and protected business foundation. Fourth, debt planning and management Fifth, set targets and evaluate business.